Bridging Cultures: The Role of Qatari Heritage Districts in Promoting Cultural Interactions, Acculturation, and Identity Formation Among Malayalee Migrants - Lakshmi Venugopal Menon (Gulf Education and Social Policy Review)
This paper examines the interaction of Indian Malayalee migrants with Qatari heritage districts highlighting the latter’s role in fostering cultural integration, acculturation, and identity negotiation. Through a case study of a three-generation Malayalee family, the author explores the varying degrees of engagement between short- and long-term migrants, emphasizing the sociocultural and psychological impacts of heritage districts. The findings reveal that while short-term migrants engage in a surface-level exploration of cultural spaces, long-term migrants develop deeper connections, integrating these districts into their lives and forming meaningful relationships with local culture. This paper also explores and underscores the challenges of maintaining cultural identity and belonging in a transnational multicultural setting, illustrating how heritage districts become spaces for cultural exchange.